2002
DOI: 10.7748/paed.14.8.30.s22
|View full text |Cite
|
Sign up to set email alerts
|

Introducing a protocol for procedural pain

Abstract: Children endure painful experiences while in hospital, often without understanding why. This study aimed to assess whether the use of a protocol for assessing, preparing and distracting children during procedures such as cannulation would decrease levels of pain and distress reported by children, parents and nurses. Pain thermometers and 'scary faces' were used as tools to assess pain and anxiety levels of 82 children. The results were ambiguous and inconsistent. However, nurses have a responsibility to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Nurses also have four essential responsibilities: promoting health, preventing illness, restoring health, and alleviating suffering, which are quality requirements for Swedish registered nurses (Swedish National Board of Health and Welfare, 2005, p. 17). Furthermore, a part of a nurse's work is to ensure that the patient's pain is minimized (McCabe, 1997), and in the case of a child, one additional important aspect is to relieve the child's anxiety and worry because these experiences can intensify their feelings of pain (Wood, 2002). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses also have four essential responsibilities: promoting health, preventing illness, restoring health, and alleviating suffering, which are quality requirements for Swedish registered nurses (Swedish National Board of Health and Welfare, 2005, p. 17). Furthermore, a part of a nurse's work is to ensure that the patient's pain is minimized (McCabe, 1997), and in the case of a child, one additional important aspect is to relieve the child's anxiety and worry because these experiences can intensify their feelings of pain (Wood, 2002). …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, nurses have a responsibility for supporting children to cope with NRMP and any potential negative effects (Melhuish & Payne, 2006; Wood, 2002). There are a number of different strategies for helping children during NRMP and Blount et al (2006) divide actions into the use of medical, psychological, and merged activities, whereas the review by Uman et al (2006) shows that nurses can support children by using hypnosis, distraction, and cognitive behavioral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that infants engaged in distraction and that distraction reduced their behavioral distress. [10] Nursing implications…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the decreased viscosity was thought to help mobilize secretions and clear the airway (Özden et al, 2009;Morrow et al, 2004;Owen et al, 2016). However, current evidence shows that NS instillation can have potentially harmful effects, such as cardiac dysrhythmias (Gardner et al, 2009;Celik & Kanan, 2006;AARC Clinical Practice Guidelines, 2010), hypoxemia and desaturation (Gardner et al, 2009;Celik & Kanan, 2006;AARC Clinical Practice Guidelines, 2010;Leddy et al, 2015;Reeve et al, 2007;Akgül et al, 2002), atelectasis (AARC Clinical Practice Guidelines, 2010; Leddy et al, 2015;Ayhan, 2015), bronchospasm (Gardner et al, 2009), worsening dyspnea (Reeve et al, 2007;O'Neal et al, 2001), tachycardia infection (Gardner et al, 2009;Celik & Kanan, 2006;AARC Clinical Practice Guidelines, 2010), trauma to mucosal linings and airway cilia (Gardner et al, 2009), hypertension (Celik & Kanan, 2006;Akgül et al, 2002), increased intracranial pressure (Gardner et al, 2009;Celik & Kanan, 2006;Akgül et al, 2002) and anxiety and discomfort (Reeve et al, 2007;Ayhan et al, 2015;Blackwood, 1999;Halm et al, 2008;Ireton, 2008).…”
Section: Introductionmentioning
confidence: 99%